Oil Risks and Firm Attributes in Oil Share Prices: Empirical Evidence from Bursa Malaysia - Safian, Dayana (2010)
This research aims to analyze the oil risks and firm attributes that could affect the share prices of oil and gas companies in Malaysia. Most of the studies conducted in regards to the oil and gas sector takes into account the contributing factors such as the condition of oil futures in NYMEX and focuses on prominent oil exporting and importing countries. In contrast, this paper empirically assesses the dynamics of global, national and company level factors that could influence the share prices of oil and gas listed companies in Bursa Malaysia. This study employed time series and panel data analysis in analyzing Malaysia’s data within the daily duration of June 1st, 2005 until May 29th, 2009. The empirical results show that the global oil demand is positively associated to the oil price and that the oil price is positively related to the condition of oil futures traded in Bursa Derivatives. Furthermore, the global oil demand, Bursa Derivatives oil futures, earnings per share and price to book are positively associated while the price to earnings ratio is negatively associated to the share prices of oil and gas companies listed in Bursa Malaysia. The practicality and valuable attribute of the results obtained from the study can be further analyzed by investors and market analysts in gaining a better understanding of the trading of share prices of oil and gas companies in Malaysia.